Francis L. Moore letter to Thomas H. Kent and Carl J. Bendorf regarding bird sightings, spring 1985 - Moore, Francis L.et al (1985)
The letter discusses field notes for spring 1985 and slides of a Curlew Sandpiper. The letter includes field note forms listing bird sightings by Moore and others and a note describing the appearance and behavior of Western Sandpipers spotted by Moore. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1985. Epson - sheet feed